Instrumen Zakat Sebagai Sumber Penerimaan dan Pengeluaran Keuangan Negara - Onti Laura Citra; Yuyun Yuniara; Idia Jonionda Piolita; Andi Cahyono (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract“This study discusses the essence of zakat as an Islamic financial instrument in the view of Muhammad Nejatullah Siddiqi. The results of this study show that Muhammad Nejatullah Siddiqi is one of the contemporary Islamic economists from the mainstream class. Thoughts about zakat are always related to Islamic economics. Zakat is the obligation of the rich, the right of the poor, and the state has an important role in managing it. It contains moral, social, and economic aspects. Zakat is the axis and center of state finance. Its position on the one hand can be a potential source of poverty alleviation, on the other hand it can be a working capital for the poor so they can open up jobs. It can even be used as the last shield for the economy so that it does not sink when consumption capacity stagnates. Keywords; Muhammad Nejatullah Siddiqi, Zakat, and Islamic Economics Abstrak“Studi ini membahas tentang esensi zakat sebagai instrumen finansial Islami dalam pandangan Muhammad Nejatullah Siddiqi. Hasil studi ini memperlihatkan bahwa Muhammad Nejatullah Siddiqi merupakan salah satu ekonomi Islam kontemporer dari golongan mainstrem. Pemikiran tentang zakat senantiasa terkait dengan ekonomi Islam. Zakat merupakan kewajiban orang-orang kaya, hak orang-orang miskin, dan negara mempunyai peran penting dalam pengelolaannya. Di dalamnya mengandung aspek moral, sosial, dan ekonomi. Zakat adalah poros dan pusat keuangan negara. Kedudukannya satu sisi dapat menjadi sumber potensial untuk mengentaskan kemiskinan di sisi lain dapat menjadi modal kerja bagi orang miskin agar dapat membuka lapangan pekerjaan. Bahkan dapat dipergunakan sebagai perisai terakhir bagi perekonomian agar tidak terpuruk ketika kemampuan konsumsi mengalami stagnasi. Kata Kunci; Muhammad Nejatullah Siddiqi, Zakat, dan Ekonomi Islam